2013
DOI: 10.20533/ijcdse.2042.6364.2013.0182
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Component of Improving Education in Less-Developed Countries: Assessment for Learning

Abstract: Global policymakers are increasingly promoting the improvement of standardized examinations in developing countries, but the role of teacher-made classroom-based assessments is often ignored. Our research experience with the Intel® Teach professional development programs and other programs suggests that such approaches have great potential to provide students and teachers with feedback to guide and deepen learning. In this paper, we review the existing literature on assessment for learning in developing countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…This finding is in line with that of M. Simon & R. Forgette-Giroux [29, p.18] indicated that the comprehensive feedback given by the headings is useful for the improvement of students at both the aggregate and individual student levels. Similarly, D. Light & E. A. Pierson [12] argued that portfolios assess the student's ability to apply expertise before merely rehearsing it. The authors added that they are fundamental apparatus for students' learning assessment of products and process supports the finding of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in line with that of M. Simon & R. Forgette-Giroux [29, p.18] indicated that the comprehensive feedback given by the headings is useful for the improvement of students at both the aggregate and individual student levels. Similarly, D. Light & E. A. Pierson [12] argued that portfolios assess the student's ability to apply expertise before merely rehearsing it. The authors added that they are fundamental apparatus for students' learning assessment of products and process supports the finding of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant aspect and value of the portfolio evaluation is that, rather than being a snapshot of student information at one point in time (like a single standardized test), it draws attention to student initiative, progress and success over a given period of time. According to D. Light & E. A. Pierson [12], Portfolios assess the student's ability to apply information rather than just rehearsing it. Since the portfolio allows data to be collected from a number of sources: parents of students, employers, teachers, and themselves, it enables teachers to provide accurate information about the student.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation